Management, Supervision and Participation of Historic Coastal Communities a Development of Mangrove Education Park Tourism in Perupuk Village, Fifty Hilir District, Regency Coal - Dian Septian Sari (Budapest International Research and Critics University, 2021)
The purpose of this study was to analyze the management of community-based mangrove ecotourism in the development of historical coastal ecotourism in Perupuk Village, Lima Puluh Pesisir District, Batu Bara Regency. To analyze the Management, Supervision, and Participation of Historical Coastal Communities in the Development of Mangrove Educational Park Tourism in Perupuk Village, Lima Puluh Pesisir District, Batu Bara Regency. There is a positive and significant influence simultaneously (simultaneous) management, supervision, and community participation on the development of coastal mangrove education tourism. There is a negative and insignificant (partial) influence on management on the development of mangrove education tourism at Historical Beach. There is a positive and significant (partial) effect of supervision on the development of coastal mangrove educational tourism. There is a positive and insignificant (partial) influence of community participation on the development of coastal mangrove education tourism.